Finite Element Model of the Effect of Optic Nerve Sheath Anisotropy on Ocular Loading During Horizontal Duction - Somaye Jafari; Shengqiang Cai; Joseph L. Demer (Bioengineering, 2025)
Previous models of extraocular mechanics have often assumed isotropic properties for ocular tissues, despite evidence indicating anisotropy in the optic nerve sheath (ONS). To investigate this further, we developed a finite element model (FEM) of horizontal eye rotation using MRI data from a living subject with normal tension glaucoma. Mechanical properties were derived from tensile tests on 17 post-mortem human eyes, revealing previously unrecognized anisotropic characteristics in the ONS. We simulated ±32° horizontal eye rotations and compared isotropic versus anisotropic ONS properties using the Holzapfel model. Strain distributions in the optic nerve (ON) were analyzed using ABAQUS 2024 software. During 32° adduction, stress and strain were concentrated at the ONS-sclera junction, reaching 8 MPa and 40% with isotropic properties, and 15 MPa and 30% with anisotropic properties. In contrast, during 32° abduction, stress was lower and strain was higher in the isotropic case (6 MPa and 30%) compared to the anisotropic case (12 MPa and 25%). Increased intraocular and intracranial pressures had minimal impact on the mechanical responses. These findings suggest that the anisotropic properties of the ONS increase stress concentration at the optic disc while reducing strain during eye movements, offering new insights into ocular biomechanics. A novel phenomenon emerged from the simulations: during larger ductions, the peripapillary Bruch’s membrane is predicted to wrinkle, forming undulations with an approximately 20 μm amplitude and 100 μm wavelength at its interface with the retina and choroid.